The Effects of interaction of leadership and followership based on followers' perceptions: Relationships among leader-member exchange, organizational citizenship behavior, work engagement, and job performance - Sheng Wen Liu (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2023)
The success of an organization cannot depend solely on leaders or followers. In past research, more attention has been paid to leaders. However, the success of an organization may depend more on followers; and even a harmonious relationship between leaders and followers. This study aims to focus on the Interaction of Leadership and Followership (ILF) perceived by different types of followers; the behavioral patterns generated by such interaction; and the impact of their interpersonal interaction on organizational citizenship behavior, work engagement, and job performance. Furthermore, the mediating effect of Leader-Member exchange (LMX) on the relationship among ILF, Organizational Citizenship Behavior (OCB) and Job Performance (JP); ILF, Work Engagement (WEng) and job performance. There were four styles of followership matched with four styles of leadership, and 16 groups of leadership and followership style interaction combinations were obtained in this study. The study found the interaction of different leadership and followership had positive, negative, and non-impact on OCB, WEng and JP. Future research can examine the interactions between more different types of leadership and followership characteristics to understand their impact on different working variables, Sand to better understand the impact of the interaction between leaders and followers.